Management Of Financing In Improving Facilities and Infrastructure (Pengelolaan Pembiayaan Pendidikan dalam Meningkatkan Sarana dan Prasarana) - Sulkarnain Sulkarnain; Syamsuddin Syamsuddin (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to determine the management of financing in improving facilities and infrastructure. This research includes the sources of funding owned, the allocation of the education budget in improving facilities and infrastructure, and the absorption or use of the budget in improving facilities and infrastructure. This type of research is qualitative and uses a case study approach. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used by the researcher is based on the theory of Miles and Huberman, namely, data collection, data reduction, data display, and verification and drawing conclusions. The validity of the data used triangulation methods, namely technical triangulation and source. The results of this study indicate that: the source of funds comes from the government in the form of Islamic Boarding School Operational Assistance funds obtained through the proposals made. Then sourced from the parents of the boarding students called Islamic Boarding School Compulsory Alms. All budget allocations come from the RAPB that has been prepared, which includes planning, procurement, and elimination of facilities and infrastructure. Budget absorption in the Islamic School if there is a process of using the budget.Kata Kunci: Education Financing Management, Facilities and Infrastructure